The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3171/2013.5.focus13163
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approach for the treatment of intradural spinal pathology

Abstract: Object A wide variety of spinal intradural pathology traditionally has been treated from a midline posterior laminectomy using standard microsurgical techniques. This approach has been successful in treating the pathology; however, it carries a risk of postoperative complications including CSF leakage, wound infection, and spinal instability. The authors describe a minimally invasive surgical (MIS) approach to treating spinal intradural pathology with a low rate of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
0
35
1
Order By: Relevance
“…While not statistically significant, there was a trend towards a reduction in blood loss in the hemilaminectomy group compared to the laminectomy group. This result was in contrast to published reports which showed a reduction in blood loss when utilizing MIS techniques for hemilaminectomy [14,21]. This finding suggests that the level of bony resection is not the major source of blood loss in these cases, and that the approach to the spine, MIS techniques versus open, may play a larger role in reducing total blood loss.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…While not statistically significant, there was a trend towards a reduction in blood loss in the hemilaminectomy group compared to the laminectomy group. This result was in contrast to published reports which showed a reduction in blood loss when utilizing MIS techniques for hemilaminectomy [14,21]. This finding suggests that the level of bony resection is not the major source of blood loss in these cases, and that the approach to the spine, MIS techniques versus open, may play a larger role in reducing total blood loss.…”
Section: Discussioncontrasting
confidence: 91%
“…Recent trends towards MIS techniques and cost-effective utilization of limited hospital resources have introduced questions regarding which surgical approaches should be used to access spinal pathologies. Moreover, multiple studies have confirmed the potential for reduced estimated blood loss, and lower length of hospital stays with MIS techniques [1,5,8,[14][15][16][17]20]. These favorable results are typically attributed to the minimal disruption of the posterior tension band with little mention of the effects of the extent of bony resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive approaches for intradural tumors have been found to be safe and effective. [1][2][3][4][5] A microscope 6 or endoscope 7 has been used recently in such cases. Minimally invasive surgical (MIS) approaches using expandable or nonexpandable tubular retractor 8 or interlaminar approaches 9 have been described to reduce trauma-related instability with comparable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surgical reports demonstrated its preferred use for small and laterally located masses. Several previous studies have attempted to improve various aspects of bone work required during hemi-laminectomy to gain more exposure for the tumor resection [3,9,10].…”
Section: Discussionmentioning
confidence: 99%